Prevent Osteoporosis: Catch the Silent Thief - Linda B. Bobroff (EDIS)
Revised! FCS-8145, a 10-page factsheet by Linda Bobroff, provides statistics and facts about osteoporosis and information about how to stop this "silent thief" of bone density. Includes calcium-rich recipes. Revised to reflect new statistics. Published by the UF Department of Family, Youth and Community Sciences, April 2007.